Lethal cerebral hemorrhage after ticagrelor intoxication: a specific antidote is urgently needed. (2nd December 2018) - Willeman, Théo; Marlu, Raphael; Böhle, Holger; Francony, Gilles; Jourdil, Jean-François; Fonrose, Xavier; Stanke-Labesque, Françoise
Abstract: Background: Ticagrelor is a direct and reversible competitive antagonist of the P2Y12 receptor and inhibits platelet activation. Although adverse bleeding is common, fatal intoxication has never been documented. Case description: A 47-year-old man died from a severe cerebral hemorrhage secondary to a fall and cranial trauma 4 d after the massive intake of ticagrelor. Iterative platelet transfusions did not improve his condition. Toxicological analyses by liquid chromatography tandem mass spectrometry (LC-MS/MS) revealed high plasma concentrations of ticagrelor (3343 µg/L) and its active metabolite AR-C124910XX (656 µg/L) 10 h after intake. The approximate ingested dose was extrapolated to 1677 mg. Assessment of ADP-induced platelet aggregation and platelet Vasodilator Stimulated Phosphoprotein phosphorylation (VASP), 2 and 3 d after admission, respectively, showed the persistence of platelet inhibition. Discussion: To the best of our knowledge, no prior fatal cases have been reported and documented with both ticagrelor and AR-C124910XX concentrations. Our findings highlight the need for a specific antidote to manage such complications resulting from ticagrelor overdose.